2016
DOI: 10.1111/cbdd.12707
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Synthesis, Characterization, and Preclinical Evaluation of 99mTc‐Labeled Macrobicyclic and Tricyclic Chelators as Single Photon Emission Computed Tomography Tracer

Abstract: The novel tetraaza macrobicyclic chelator 3,6,9,15-tetraazabicyclo[9.3.1]pentadeca-1(15),11,13-triene-2,10-dione (TBPD) and pentaaza macrotricyclic chelator 9-oxa-3,6,12,15,21-pentaazatricyclo[15,3,2,1]trieicos-1(21),17,19-triene-2,7,11,16-tetradione (OPTT) were synthesized, characterized, and radiolabeled with (99m)Tc to produce (99m)Tc-TBPD and (99m)Tc-OPTT. These radiolabeled complexes were prepared with high radiolabeling yield, radiochemical purity, and good in vitro stability up to 24 h. The labeling eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
(22 reference statements)
0
6
0
Order By: Relevance
“…Tetraazamacrocycle derivatives are widely studied as bifunctional chelating agents for conjugating different biomolecules with radionuclides in target-specific radiotherapy. The novel tetraazamacrobicyclic chelator 3,6,9,15-tetraazabicyclo[9.3.1]pentadeca-1(15),11,13-triene-2,10-dione (TBPD) and pentaazamacrotricyclic chelator 9-oxa-3,6,12,15,21-pentaazatricyclo[15,3,2,1] trieicos-1(21), 17,19-triene-2,7,11,16-tetradione (OPTT) ( Figure 2 ) were synthesized and radiolabeled with 99m Tc to produce 99m Tc-TBPD and 99m Tc-OPTT [ 94 ]. These radiolabeled complexes showed high yield, purity, labeling efficiency and in vitro stability.…”
Section: Spacers Chelators and Radionuclidesmentioning
confidence: 99%
“…Tetraazamacrocycle derivatives are widely studied as bifunctional chelating agents for conjugating different biomolecules with radionuclides in target-specific radiotherapy. The novel tetraazamacrobicyclic chelator 3,6,9,15-tetraazabicyclo[9.3.1]pentadeca-1(15),11,13-triene-2,10-dione (TBPD) and pentaazamacrotricyclic chelator 9-oxa-3,6,12,15,21-pentaazatricyclo[15,3,2,1] trieicos-1(21), 17,19-triene-2,7,11,16-tetradione (OPTT) ( Figure 2 ) were synthesized and radiolabeled with 99m Tc to produce 99m Tc-TBPD and 99m Tc-OPTT [ 94 ]. These radiolabeled complexes showed high yield, purity, labeling efficiency and in vitro stability.…”
Section: Spacers Chelators and Radionuclidesmentioning
confidence: 99%
“…The UV spectroscopy was measured by using microplate spectrophotometer (Multiskan GO, Thermo Fisher, USA). 1 HNMR spectra were measured on a Bruker (600 MHz) spectrometer. Chemical shifts are reported in δ (ppm) values.…”
Section: Chemicals and Equipmentsmentioning
confidence: 99%
“…Nuclear medicine relies on collaboration of radiopharmaceuticals and nuclear medicine technologies. Substantial effort has been focused on the development of molecular probes to achieve tumor‐specific therapeutic and diagnostic agents . Antibody, sugar, folic acid (FA), transferrin, epidermal growth factor, and Arg–Gly–Asp peptide are tumor targeting ligands used to give an active targeting ability to drug carriers .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wen et al (2006) reported the crystal structure of N,N 0 -bis(4-methoxyphenyl)-3-oxapentanediamide which was synthesized using oxydiacetic acid and p-methoxyaniline. A macrotricyclic compound containing oxydiacetic acid moiety was synthesized and radiolabelled with 99m Tc, which provided a platform for the development of imaging agents and the diagnosis of tumour cells (Yadav et al, 2016). Yasodhai & Govindarajan (2000) reported the synthesis and thermal study of hydrazinium oxydiacetate.…”
Section: Introductionmentioning
confidence: 99%